Low insertion loss of surface mount device low pass filter at 700 MHz - Khairil Anuar, Khairi; Mohd Faizal, Jamlos; Surentiran, Padmanathan; Mohd Aminudin, Jamlos; Muammar, Mohamad Isa (IAES, 2019)
The paper involved with the design, simulation and fabrication of 6th order elliptical-based Surface Mount Device (SMD) LPF with cutoff frequency at 700 MHz. Fabricated LPF is consisted of four PCB layers which components of SMD are soldered on the top layer. Another three layers is for grounding and shielding, power supply and grounding void. The four layers is crucial to avoid interference between components. The research has find out that the momentum simulation is definitely required to improve the signals response compared to a normal simulation by ADS software. The comparison between momentum simulated versus measured and normal simulated versus measured is 0.2 dB and 29 dB correspondingly. Such huge difference leads to conclusion that momentum simulation is saving time without having much struggles and efforts to get optimum readings. The Proposed SMD LPF has a very low insertion loss of 0.965dB with a transition region of 195 MHz which is good steepness to avoid any image frequency.